Effectiveness of Self-Management Education based on Information Technology (IT) in Chronic Kidney Disease Patients - Innani Wildania Husna; Qolbi Nur Qoidah Yahya; Masita Widiyani; Sholihin Sholihin (Jurnal Ners, 2019)
Introduction: Chronic Kidney Disease (CKD) has a slow progression in the treatment process. The use of IT (information technology) media as an innovation to support health education in patients with chronic kidney failure to improve their knowledge and self-management nowadays is becoming a trend.Methods: We analyzed the literature to identify the effectiveness of IT using as education media on chronic kidney disease patients. Articles were obtained by PRISMA approach from Scopus, ScienceDirect, CINAHL, PubMed, and Proquest limited to the 5 years; from 2013 to 2018 and obtained 12 articles with RCTs design study. We identified interventions based on IT devices such as smartphones, PDAs (Personal Digital Assistant), computer-based applications, telehealth, film, SMS, and website-based applications.Results: This studies assessed 12 journals. According to the outcomes, there were 38 outcomes in total which are divided into three groups. They were 13 clinical outcomes, 14 caring process outcomes, and 11 usability and feasibility outcomes.Conclusion: Overall, the percentage of intervention which had a positive effect on the outcomes was about 47%. Smartphone and computer-based technologies are the most effective to help the patient find information about aspects related to caring, self and disease management which are recommended by the health care team.